Development Of a Persuasive and Universal Wearable Device to Promote Healthy Behavior and Enhance Exercise Self-Efficacy - Yansen Theopilus; Johanna Octavia; Thedy Yogasara (University of Technology Yogyakarta, 2021)
Exercising is a key activity to prevent diseases and strengthen our immune system. Unfortunately, people often find it difficult to have healthy behavior, especially for exercising regularly. There are some reasons for that problem, such as lack of exercise knowledge, lack of equipment, lack of available time and space, lack of exercise partner, and poor physical conditions. This behavior problem would make people vulnerable to illness. Therefore, this research aims to develop a wearable device to assist users’ exercise activity and encourage them to have exercise self-efficacy while ensuring a positive experience. The device development method used a combination of persuasive design, universal design, and rich experience design approach. The persuasive approach aims to design the product that can change the behavior problem into the behavior goal, while the universal design principle ensures that the device suits various user characteristics. We also use a rich experience design approach to generate a positive experience from negative emotions. This research has invented a smart exercise band that acts as an exercise instructor, partner, and reminder that recommends various personalized exercise programs according to the user characteristics (gender, age, physical condition, schedule, and other preferences). The device was evaluated using Task Completion Method, Retrospective Thinking Aloud, and Perceived Persuasiveness Questionnaire to assess the usability, persuasiveness, and experience. The evaluation results have shown that the product has good usability, effective persuasion, and positive experience.